Mind the gap, dash & lily eaudiobook - Cohn, Rachel (Dash & Lily Series, 2020)
For Dash and Lily, it's beginning to look a lot like...distance! Just in time for the series release of Dash & Lily on Netflix comes a new helping of love—this time across the pond as best-selling authors Rachel Cohn and David Levithan send Dash and Lily to England. Dash and Lily were feeling closer than ever...it's just too bad they're now an ocean apart. After Dash gets accepted to Oxford University and Lily stays in New York to take care of her dogwalking business, the devoted couple are struggling to make a long distance relationship work. And when Dash breaks the news that he won't be coming home for Christmas, Lily makes a decision: if Dash can't come to her, she'll join him in London. It's a perfect romantic gesture...that spins out of Lily's control. Soon Dash and Lily are feeling more of a gap between them, even though they're in the same city. Will London bring them together again—or will it be their undoing?